Assessing the 'value' of new transport initiatives in deprived neighbourhoods in the UK - Lucas, K; Tyler, S; Christodoulou, G (Elsevier, 2009)
In the context of growing policy awareness in the UK of the links between transport and social exclusion, this paper describes case-study research of four different transport projects funded under the UK Department for Transport's Urban Bus Challenge Fund (UBC) with the specific aim of facilitating social inclusion in the areas they serve. Through surveys and interviews with end-users, the study qualitatively and quantitatively evaluated the value of these new services to local residents in terms of their increased economic opportunities and other quality of life benefits. It also aimed to identify their wider contribution to the renewal and regeneration of the deprived areas they serve through depth interviews with professional local stakeholders.